Sieving Machine Calibration Using a Profile Projector with Standard Method ASTM E-11 2004 - Badri, Muftil; Arief, Dodi Sofyan; Solih, Aji Mahmud; Ayunita, Dyna; Muflihana, Afdila (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2018)
Sieving machine is used to sift material of sand and stone previously mixed. Sieve machine is a measuring instrument to determine the size of sand grains that can be used in building construction. The purpose of this research is to calibrate the sieving machine using profile projector with standard method ASTM E-11 2004. Based on this research, the conclusion of calibration data of sieving machine has been obtained. It was found that the sieving machine used in this research can be used to determine the size of sand grains used for construction. The uncertain value of the width opening sieve is 15.8 Î¼m and the diameter of wire is 0.02 mm, so that the value of evaluation is lower than the allowed geometry deviation limit. Thus it can be concluded that the sieve machine is still within the permissible geometry tolerance limit.